2023
DOI: 10.1007/s12671-023-02128-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief Online Mindfulness-Based Intervention for University Students

Abstract: Objectives The COVID-19 pandemic resulted in a dramatic increase in Web-based education, lacking face-to-face student–teacher and student–student interaction, and consequently impairing students’ sense of belonging to a community, interoceptive awareness, and academic self-efficacy. This study examined how a brief mindfulness-based intervention in an online university course can be effective in enhancing attention resources, developing a stronger sense of academic self-efficacy, and improving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Finally, 37 reports were assessed for eligibility, out of which 16 were excluded, after completing this evaluation, the remaining articles were carefully analyzed to determine their eligibility. As a result, 21 articles were identified that met the established inclusion criteria ( Figure 1 ) ( 24 , 30 49 ), 17 of these studies underwent quantitative synthesis in the form of meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 37 reports were assessed for eligibility, out of which 16 were excluded, after completing this evaluation, the remaining articles were carefully analyzed to determine their eligibility. As a result, 21 articles were identified that met the established inclusion criteria ( Figure 1 ) ( 24 , 30 49 ), 17 of these studies underwent quantitative synthesis in the form of meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review, selected articles corresponding to randomized controlled clinical trials published in English in the last decade were included, with the following distribution of years: 2013 ( 35 ), 2014 ( 37 , 39 , 47 ), 2016 ( 30 , 39 ), 2017 ( 38 , 40 ), 2018 ( 31 ), 2020 ( 32 , 43 , 45 ), 2021 ( 36 , 44 , 46 , 48 , 49 ), 2022 ( 33 , 42 ), and 2023 ( 24 , 34 ). The countries of origin of the articles include Spain with four articles ( 32 , 34 , 47 , 49 ), three articles from the USA ( 37 , 42 , 43 ), two from China ( 44 , 46 ), two from Canada ( 45 , 48 ), and one from each of the following countries: Taiwan ( 30 ), Australia ( 31 ), the United Kingdom ( 24 ), Switzerland ( 33 ), Norway ( 35 ), Brazil ( 36 ), Singapore ( 38 ), Germany ( 39 ), Netherlands ( 40 ), and South Korea ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations